The in vitro effect of cypermethrin on quality and oxidative stress indices of rainbow trout Oncorhynchus mykiss spermatozoa - Kutluyer, Filiz; Benzer, Fulya; Erisir, Mine; Ogretmen, Fatih; Inanan, Burak Evren (Academic Press Inc Elsevier Science, 2016)
There is limited information on the scientific literature about the effect of in vitro exposure of fish sperm to pesticides. In vitro effect of cypermethrin on sperm quality and oxidative stress has not yet been fully investigated. Therefore, the effects of cypermethrin, a type II pyrethroid insecticide, on quality and oxidative stress of spermatozoa were examined in vitro. To explore the potential in vitro toxicity of cypermethrin, fish spermatozoa were incubated with different concentrations of cypermethrin (1.025, 2.05 and 4.1 mu g/l) for 2 h. The motility rate and duration of sperm were determined after exposure to cypermethrin. Reduced glutathione (GSH), glutathione peroxidase (GSH-Px), catalase (CAT) and malondialdehyde (MDA) in spermatozoa were analyzed for determination of oxidant and antioxidant balance. Our results indicated that spermatozoa motility and duration significantly decreased with exposure to cypermethrin. Additionally, activity of GSH-Px (P < 0.05) and MDA and GSH levels increased in a concentration-dependent manner while CAT activity decreased (P < 0.05). Consequently, the oxidant and antioxidant status and sperm quality were affected by quantitative changes and different concentrations of cypermethrin. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Cypermethrin; Rainbow trout; Oncorhynchus mykiss; Spermatozoa; Oxidative stress indices; Sperm quality